1997
DOI: 10.1212/wnl.49.2.623
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroiditis and a rapidly progressive dementia: Global hypoperfusion on SPECT scanning suggests a possible mechanism

Abstract: We report the clinical, laboratory, EEG, and SPECT findings in a 59-year-old euthyroid woman with previously undiagnosed autoimmune thyroiditis, subclinical hypothyroidism, and rapidly progressive dementia. We made a diagnosis of Hashimoto's encephalopathy based on elevated thyrotropin, abnormal EEG, and clinical improvement after thyroid hormone replacement. SPECT demonstrated global hypoperfusion with normalization on clinical recovery, suggesting a possible mechanism for the pathogenesis of Hashimoto's ence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 5 publications
2
94
0
7
Order By: Relevance
“…Conversely, depression may be accompanied by various subtle thyroid abnormalities. Relatively few previous functional neuroimaging studies have investigated the neural correlates of mood dysfunction in patients with hypothyroidism (Bauer et al 2009;Constant et al 2001;Nagamachi et al 2004;Schraml et al 2006;Zhu et al 2006), and these studies reported cerebral hypoperfusion as the most consistent finding (Bauer et al 2009;Constant et al 2001;Forchetti et al 1997;Kinuya et al 1999;Krausz et al 2007;Krausz et al 2004;Nagamachi et al 2004;Schraml et al 2006). In a subgroup of patients, this hypoperfusion subsided after thyroid replacement therapy (Bauer et al 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Conversely, depression may be accompanied by various subtle thyroid abnormalities. Relatively few previous functional neuroimaging studies have investigated the neural correlates of mood dysfunction in patients with hypothyroidism (Bauer et al 2009;Constant et al 2001;Nagamachi et al 2004;Schraml et al 2006;Zhu et al 2006), and these studies reported cerebral hypoperfusion as the most consistent finding (Bauer et al 2009;Constant et al 2001;Forchetti et al 1997;Kinuya et al 1999;Krausz et al 2007;Krausz et al 2004;Nagamachi et al 2004;Schraml et al 2006). In a subgroup of patients, this hypoperfusion subsided after thyroid replacement therapy (Bauer et al 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Vas kü li tin anji yog ra fik ve bi yop si bul gu la rı, bu has ta lık ta çok net ola rak tes pit edi le me di ği için bu me ka niz ma halen tar tış ma lı ol sa da SPECT (single photon emission computed tomography) ile be yin de dif füz homo jen glo bal hi po per füz yon gös te ril miş ve im mun komp leks ve ya an ti kor bi ri ki mi ile mik ro do la şı mın bo zul du ğu dü şü nül müş tür. 2 Bu bo zul ma, glo bal hipo per füz yo na yol aça rak en se fa lo pa tik de ği şik likle re ne den olur. 1966 yı lın da ta nım lan dı ğın dan be ri bu tab loy la sey re den na dir ol gu lar "Has hi moto En se fa lo pa ti si " ola rak li tera tür de yer al mış tır.…”
Section: Otoimmün Tiroiditle İlişkiliunclassified
“…Ge nel lik le 3-7 gün bo yun ca yük sek doz in tra ve nöz me til pred ni zo lon (1 g/gün) ya da yük sek doz oral pred ni zo lon (50-150 mg/gün) kul la nı lır ve ti pik ola rak kor ti kos te ro id teda vi si nö ro lo jik semp tom lar da be lir gin dü zel me sağ la nır. 2,12 Azat hi op ri ne, sik lo fos fo mid, in tra ve nöz im mung lo bu lin ve plaz ma fe rez de kul la nı lan da ha az sa yı da ol gu da ba şa rı lı so nuç lar ver miş tir. 13 Has himo to en se fa lo pa ti si için öne ri len di ğer te da vi ler, tiro i di et ki le yen ajan lar (ço ğun luk la le vo ti rok sin) ve nö bet olur sa an ti e pi lep tik ilaç la rı içe rir.…”
unclassified
“…[7][8][9] Global hypoperfusion on single-photon emission computed tomography (SPECT) studies has also been reported. 10,11 Patients with HE may have nonspecific evidence of inflammation, including an elevated ESR, CRP, and CSF protein. 12 Other laboratory abnormalities may include a mild elevation of liver aminotransferase levels; renal impairment has also been reported in a few cases of HE in the form of glomerulonephritis, and may be related to deposition of immune complexes containing thyroglobulin antigen.…”
Section: Commentarymentioning
confidence: 99%